I Don’t Belong Here (Comparative & International Education Series, 2022)
I felt so proud to be accepted on a full scholarship at a university in the United States to pursue my doctoral degree. I had a wonderful career of 10 years as a teacher in international schools in the Middle East. I had a good life, I had travelled to over 40 countries, I had all sorts of adventures; and somehow, for the life of me, I do not know what possessed me to start my PhD. Anyway, there was no time for regrets or looking back because here I was making it official, by attending orientation for new graduate students (or so I thought). I read that email three times, just to make sure I had the right time and place.